The original query is to find x(t) with a Laplace transform of X(s) = 4(s+1) / s(s+2)^2. The poles are s_1 = 0 and s_2 = -2 (with a multiplicity of 2).

Because the second pole is not simple, its x(t) should be solved via the Decomposition Theorem, correct?

I.e. lim(s->s_{2}) = d/ds [ X(s) (s-s_{2})^2 e^st ]

Continuing to solve, I reach the following and am unsure of how to continue:

$$ lim_{(s->s_{2})} \frac{d}{ds} \left(\frac{4(s+1)}{s}\right) * e^st $$

Because x(t) for the first pole is x(t) = 1, and x(t) for the second (non-simple pole) is x(t) = (2t-1)*e^(-2t), the final solution is the sum of the two:

$$ x(t) = 1 + (2t-1)*e^(-2t) $$

How is this reached (i.e. how is the solution for the second pole reached, from the point where I left off)?


You should do a partial fraction expansion (also named partial fraction decomposition) instead.

Using partial fraction expansion, you can write the Laplace domain polynomial as:

$$X(s) = \frac{4(s+1)}{s(s+2)^2} = \frac{A}{s}+\frac{B}{s+2}+\frac{C}{(s+2)^2}$$

Solving for the coefficients is simple and you can show that

$$A = 1, B = -1, C = 2$$

And so

$$X(s) = \frac{4(s+1)}{s(s+2)^2} = \frac{1}{s}-\frac{1}{s+2}+\frac{2}{(s+2)^2}$$

Doing the inverse Laplace transform term by term is easy and can be easily found in a table. The inverse Laplace transform of X(s) is now then

$$x(t) = 1 - e^{-2t} + 2te^{-2t}$$

Re-arrange the terms to get your final expression: $$x(t) = 1 + (2t-1)e^{-2t}$$

| improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.